Phytotherapy: A promising approach for the treatment of Alzheimer's disease - Ogbodo Onyebuchi John; Ihim Stella Amarachi; Agbo Precious Chinazom; Echezona Adaeze; Mayur B. Kale; Mohit D. Umare; Aman B. Upaganlawar (Elsevier, 2022)
Alzheimer's disease (AD) is a progressive neurological disease and the most common form of dementia, affecting more than 10 million people all over the world. Clinically, AD is characterized by progressive deficits in memory, cognitive impairment, and altered behavior. Although researches have largely continued, there is still no appropriate treatment option for disease-modifying AD. However, symptomatic treatment options exist. Medicinal plants have been used in different systems of medicine from ancient times for the treatment of diseases. Numerous herbs have been shown to improve brain function and may have a role to play in AD treatment. In this review, we provide a systematic review on the role of medicinal plants and herbs useful for the treatment of Alzheimer's disease, the effect of these herbs on hormones, herb-drug interactions as well as stability-related testing for the herbal pharmaceutical medicines.